2016
DOI: 10.3390/insects7020017
|View full text |Cite
|
Sign up to set email alerts
|

Pheromone Autodetection: Evidence and Implications

Abstract: Olfactory communication research with insects utilizing sex pheromones has focused on the effects of pheromones on signal receivers. Early pheromone detection studies using the silkworm moth, Bombyx mori L., and Saturniids led to the assumption that emitters, especially females, are unable to detect their own pheromone. Pheromone anosmia, i.e., the inability of females to detect their conspecific sex pheromone, was often assumed, and initially little attention was paid to female behaviors that may result from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 194 publications
(171 reference statements)
0
62
0
Order By: Relevance
“…Only the CYP genes with male antennal and olfactory specific expression, such as PdivCYP4AW1 , were verified as pheromone‐degrading enzyme genes (Maïbèche‐Coisne et al ., ). In fact, sex pheromones can be auto‐detected by female moths (Holdcraft et al ., ; Stelinski et al ., ). Receptor cells specific for sex pheromone components were also found in S. littoralis female antennae and the sensitivity of the pheromone receptors was similar to those of males, whereas the number of pheromone‐specific sensilla was much lower in females (Ljungberg et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Only the CYP genes with male antennal and olfactory specific expression, such as PdivCYP4AW1 , were verified as pheromone‐degrading enzyme genes (Maïbèche‐Coisne et al ., ). In fact, sex pheromones can be auto‐detected by female moths (Holdcraft et al ., ; Stelinski et al ., ). Receptor cells specific for sex pheromone components were also found in S. littoralis female antennae and the sensitivity of the pheromone receptors was similar to those of males, whereas the number of pheromone‐specific sensilla was much lower in females (Ljungberg et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have always excluded genes not exclusively expressed in the male antennae, which resulted in a lack of knowledge on the molecular mechanisms of sex pheromone recognition, including the olfactory receptors (Krieger et al, 2004) Only the CYP genes with male antennal and olfactory specific expression, such as PdivCYP4AW1, were verified as pheromone-degrading enzyme genes (Ma€ ıbè che- Coisne et al, 2004). In fact, sex pheromones can be auto-detected by female moths (Holdcraft et al, 2016;Stelinski et al, 2014). Receptor cells specific for sex pheromone components were also found in S. littoralis female antennae and the sensitivity of the pheromone receptors was similar to those of males, whereas the number of pheromone-specific sensilla was much lower in females (Ljungberg et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in females, the detection of the minor sex pheromone component is considered as basis for recognizing the presence of conspecific females. The ability of female moths to “autodetect” components of their own pheromone has been reported for several moth species (Holdcraft et al ., ) and it has been proposed that it may help female moths to escape competition for mating partners, ecological resources or oviposition sites (Harari & Steinitz, ). Alternatively, it is possible that “autodetection” triggers physiological responses in females.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies on Bombyx mori and other moth species have led to the notion that females are generally anosmic for their own pheromone (Schneider, ). However, over the last decades numerous electrophysiological and behavioral studies have shown for a variety of lepidoteran species (reviewed in Holdcraft et al ., ) that female moths have the ability to recognize components of the pheromone they release; this phenomenon was designated as “autodetection” (Ochieng et al ., ; Schneider et al ., ; Bakthavatsalam et al ., ). This term could suggest self‐detection of compounds released by the pheromone‐producing individual, however, all the reported cases describe a detection of pheromones released by conspecific females (Holdcraft et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation